2022
DOI: 10.3390/plants11202789
|View full text |Cite
|
Sign up to set email alerts
|

Herniarin, Dimethylfraxetin and Extracts from Tagetes lucida, in Psychosis Secondary to Ketamine and Its Interaction with Haloperidol

Abstract: Tagetes lucida Cav., is a medicinal plant used in Mexico to alleviate different disorders related to alterations of the central nervous system, such as behaviors associated with psychosis. The present work evaluated the effect of different extracts separated from this plant, TlHex, TlEA, TlMet, and TlAq, and of two isolated coumarins, herniarin (HN) and dimethylfraxetin (DF), on haloperidol-induced catalepsy (HAL), and psychotic behaviors provoked with a glutamatergic antagonist, ketamine (KET) on ICR mice. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Herniarin, a compound found in several groups of plants, has a broad range of activities that includes anti‐cancer, anti‐genotoxic, anti‐diabetic, anti‐anxiety, anti‐depressant, anti‐inflammatory, and immunomodulatory effects [27] . Studies conducted by Silvan et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herniarin, a compound found in several groups of plants, has a broad range of activities that includes anti‐cancer, anti‐genotoxic, anti‐diabetic, anti‐anxiety, anti‐depressant, anti‐inflammatory, and immunomodulatory effects [27] . Studies conducted by Silvan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Herniarin, a compound found in several groups of plants, has a broad range of activities that includes anti-cancer, antigenotoxic, anti-diabetic, anti-anxiety, anti-depressant, anti-inflammatory, and immunomodulatory effects. [27] Studies conducted by Silvan et al showed that herniarin has in vitro antiinflammatory properties [28] and suggested its potential to act as an anti-nociceptive agent in mice. [29] Barchestani et al demonstrated that herniarin has the ability to reduce memory loss and pain thresholds by counteracting oxidative stress in an animal model of ischemia.…”
Section: Effect Of Herniarin On Erk and P-erk Protein Levels In Rt112...mentioning
confidence: 99%
“…In the same work, the interaction of these natural treatments with haloperidol was identified since a potentiation of catalepsy in mice induced by that drug was observed. The results of both trials indicate that these T. lucida products modify glutamatergic and dopaminergic neurotransmission; both are involved in the pathophysiology of neurological diseases such as schizophrenia [27]. This finding is interesting since ketamine, also used as an antidepressant, can reverse the effects caused by CPZ.…”
Section: Behavioral Testsmentioning
confidence: 94%
“…Recent research has shown that different extracts of T. lucida have properties such as anti-inflammatory and antioxidant activities and mainly have a potential use against illnesses related to the CNS, providing antinociceptive and sedative effects, and treatment for disorders of depression and anxiety [17][18][19]21,23,[25][26][27][28][29]. The HPLC analysis of the TlHx and TlAcOEt extracts allowed the identification of five coumarins with biological activity: IC, HN, DF, SC, and PE.…”
Section: Quantification and Chemical Identification Of Five Coumarinsmentioning
confidence: 99%
See 1 more Smart Citation